Superior outcome of labial mucosal autograft over limbal allograft in the management of recurrent pterygium with symblepharon: a case report - Oh, Joo Youn; Khwarg, Sang In (Frontiers in Medicine, 2024)
A 40-year-old female visited our clinic for recurred pterygium and symblepharon in the right eye. She had a history of pterygium excision 8 years before. We performed pterygium excision combined initially with mitomycin C (MMC) application and conjunctival autograft and subsequently three times with limbal allografts, MMC application and amniotic membrane transplantation over the course of 7 years. All procedures were unsuccessful, resulting in aggressive recurrences of pterygial mass and symblepharon, extraocular movement limitation, corneal astigmatism and decreased visual acuity. Ultimately, we applied a labial mucosal autograft after the recession of pterygial tissue. No complications were observed. Two and a half years postoperatively, the labial mucosal autograft was well-integrated into the conjunctival surface without symblepharon, recurrence or abduction limitation. Corneal clarity was restored, and astigmatism reduced, with no recurrence of pterygium. In conclusion, labial mucosal autograft is a viable treatment option in complex cases of recalcitrantly recurrent pterygium with symblepharon.